Plan estratégico para la Asociación Solidarista de Empleados del TEC, Sede San Carlos 2015-2020 - Picado-Arias, Adriana (Instituto Tecnológico de Costa Rica, 2015)
The present project has the main objective of proposing a strategic plan for Asociación Solidarista de Empleados, Tecnológico de Costa Rica Campus San Carlos (ASET) that allows them to guide their actions during next five years. This project used a qualitative approach. Among the methods used for the development of the internal and external diagnostics of the association were tools such as internal management analysis, 7 “S” McKinsey, PEST analysis, benchmarking, and SWOT analysis. Thus, through the methodology of Balanced Scorecard and business base model, it would be possible to create the main strategies to follow according with the diagnostics. The study determined the lack of ASET strategic profile. The tool of business model summarizes the nine modules that create, provide, and attract a specific market segment. Besides, the strategic plan that was proposed is accessible and easy to implement because most of the strategies can use the association’s current resources.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2015.
Keywords: Benchmarking; Evaluación de proyectos; Análisis FODA